Toward a New Paradigm for Targeted Natriuretic Peptide Enhancement in Heart Failure - Gidlöf, Olof (Frontiers in Physiology, 2021)
Abstract The natriuretic peptide system (NPS) plays a fundamental role in maintaining cardiorenal homeostasis, and its potent filling pressure-regulated diuretic and vasodilatory effects constitute a beneficial compensatory mechanism in heart failure (HF). Leveraging the NPS for therapeutic benefit in HF has been the subject of intense investigation during the last three decades and has ultimately reached widespread clinical use in the form of angiotensin receptor-neprilysin inhibition (ARNi). NPS enhancement via ARNi confers beneficial effects on mortality and hospitalization in HF, but inhibition of neprilysin leads to the accumulation of a number of other vasoactive peptides in the circulation, often resulting in hypotension and raising potential concerns over long-term adverse effects. Moreover, ARNi is less effective in the large group of HF patients with preserved ejection fraction. Alternative approaches for therapeutic augmentation of the NPS with increased specificity and efficacy are therefore warranted, and are now becoming feasible particularly with recent development of RNA therapeutics. In this review, the current state-of-the-art in terms of experimental and clinical strategies for NPS augmentation and their implementation will be reviewed and discussed.